Synthesis, characterization of flavone, isoflavone, and 2,3-dihydrobenzofuran-3-carboxylate and density functional theory studies - Bhatti, Huma Aslam; Uddin, Nizam; Ayub, Khurshid; Saima, Bibi; Uroos, Maliha; Iqbal, Jamshed; Anjum, Shazia; Light, Mark Edward; Hameed, Abdul; Khan, Khalid Mohammed (European Journal of Chemistry, 2015)
We describe the oxidation of flavanones by employing phenyliodonium diacetate to form the flavone (15), isoflavone (8) and 2,3-dihydrobenzofurane (18) in this study. The oxidative method was found to be regioselective and dependent on the substitution pattern present on the two aromatic rings of the starting flavanone. The structures of products obtained were fully characterized by using IR, 1H and 13C NMR spectroscopy and Mass spectrometry. X-ray crystallography further confirms the structures of flavones and isoflavone. The density field theory calculations have also been performed to get more insight about the structures, electronic and spectroscopic properties of synthetic flavonoid derivatives. The geometrical parameters such as bond lengths and angels showed a good correlation with the values obtained through X-ray crystallography. Moreover, the theoretically simulated vibrational and UV-vis spectral values are in agreement with the experimental results.